Analysis Of Psychological Conflict Of The Main Character In The “The Rocking Horse Winner” Short Story - Novrianti, Febby Okta (UNIVED Press, 2025)
This research discusses psychological conflict using Anna Freud's Defense Mechanism theory in the short story “The Rocking Horse Winner”. This research has two objectives, namely to find out the defense mechanism and to find out the factors that cause the defense mechanism in the main character in the short story “The Rocking Horse Winner”. This research uses a qualitative descriptive method. This relates to the description of the data in the form of the utterances of the main character Paul in the short story. The analysis in this study using Spradley's analysis. The results of this study show that of the ten defense mechanisms, six were found, namely rationalization, displacement, repression, projection, denial, and identification. Neurotic anxiety and moral anxiety were found as two of the three factors causing defense mechanisms. In this study, the most common type of defense mechanism found is rationalization and neurotic anxiety is the dominant factor that causes the use of this defense mechanism by the main character